1973
DOI: 10.1111/j.1432-1033.1973.tb03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown‐Adipose‐Tissue Mitochondria

Abstract: 1.Endogenously uncoupled mitochondria from the brown adipose tissue of cold-adapted hamsters, rats and guinea-pigs swell in KC1, KBr, KNO, and KCNS in the presence of valinomycin. Identical rates of swelling are obtained employing the ammonium salts or the potassium salts in the presence of nigericin.2. Albumin has no effect on the swelling rates in these potassium salts plus valinomycin, but is strongly inhibitory with both potassium salts plus nigericin and wit,h ammonium salts. Albumin inhibits swelling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 25 publications
8
97
0
Order By: Relevance
“…It is interesting that non-specificity of the thermogenin-induced conductance was already recognized by its first students, Nicholls and Lindberg [28], who found that brown fat mitochondria are permeable not only to H ~ but ~lso to CI-. Garlid and co-workers [27, 29,31] reconstituted CI-transport in thermogenin proteoliposomes and ~hnwccl that, ~_!nlike in the case of H* transport, fatty anions are no: nece~:~ary for this process.…”
Section: Fatty Acid Circuit Hypothesismentioning
confidence: 97%
“…It is interesting that non-specificity of the thermogenin-induced conductance was already recognized by its first students, Nicholls and Lindberg [28], who found that brown fat mitochondria are permeable not only to H ~ but ~lso to CI-. Garlid and co-workers [27, 29,31] reconstituted CI-transport in thermogenin proteoliposomes and ~hnwccl that, ~_!nlike in the case of H* transport, fatty anions are no: nece~:~ary for this process.…”
Section: Fatty Acid Circuit Hypothesismentioning
confidence: 97%
“…Apart from other types of mitochondria they possess the uncoupling protein (UP), a unique proton translocator [2,3], converting A/~H + into heat. H + fluxes through the UP are inhibited by purine nucleotides [4][5][6][7][8] and activated by fatty acids [3,[8][9][10]. Both regulatory mechanisms were also demonstrated in a reconstituted system [3], but the activation by fatty acids was disputed in another laboratory [2].…”
Section: Introductionmentioning
confidence: 99%
“…In order to relate changes in GDP binding to the function of the proton conductance pathway, mitochondrial swelling and GDP binding were assayed on BAT mitochondria prepared from rats housed at 22 "C or at 4 "C for either 3 h or 7 days. Mitochondrial swelling, in the presence of potassium acetate and valinomycin, is an indication of the proton permeability of the mitochondrial inner membrane (Nicholls & Lindberg, 1973;Rial & Nicholls, 1984). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial permeability to protons was determined as the initial rate of swelling of non-respiring mitochondria in iso-osmotic media containing valinomycin (Nicholls & Lindberg, 1973). Mitochondria were prepared by the procedure outlined above but in 250 mmsucrose/5 mM-Tes/1 mM-EDTA, pH 7.2 at 4 'C.…”
Section: Mitochondrial Swellingmentioning
confidence: 99%